Bar load-displacement curve model based on statistical damage mechanics - Yang, Zhao; Chen, Song; Sun, Jinglai; Zheng, Yibo; Li, Liufang; Yuan, Ying (Frontiers in Earth Science, 2022)
The load displacement curve model of bolt is of great significance to estimate the ultimate uplift bearing capacity of bolt and analyze the force transmission of bolt. Therefore, it is particularly necessary to establish a high-precision load displacement curve model of bolt. In this paper, the statistical damage theory is introduced to establish a new stiffness degradation model of bolt load displacement curve, and a model which is more consistent with the test data and has higher accuracy in predicting the ultimate uplift capacity is proposed. The influence of model parameters on the model curve is analyzed. It can be concluded that the key to the load displacement curve of the anchor and the prediction of the uplift bearing capacity of the anchor is to determine the statistical random distribution characteristics of the micro element strength of the anchor interface.